Determination of Phytochemicals by GC-MS in Two Fractions (17 and 21) of Methanol Extract of Loranthus Micranthus and their Antioxidant and Anti-Inflammatory Activity - Channabasava; Melappa, Govindappa; Naik, Chandrashekhar (Natural Products Journal, The, 2015)
Loranthus micranthus, a parasitic plant of different hosts has been used for treating various diseases traditionally as it has pharmaceutically important phytochemicals. The methanol extract of L. micranthus two fractions (17 and 21) were selected based on visibility and less compounds in TLC for identification of phytochemicals in GC-MS and yielded 13 and 12 different chemical compounds respectively. The yielded compounds from each fraction have pharmaceutical importance and possess different biological activities. Each compound’s mass spectrum was given and analysed. The two fractions were evaluated for biological activities to know the efficacy of the compounds. In both, antioxidant activities (DPPH and FRAP), the fraction 17 had shown strong activity (74, 819.48± 0.05) compared to fraction 21 and standard. The albumin denaturation, membrane stabilization and proteinase activities were tested using these two fractions and fraction 17 exhibited strong activity on these tests effectively (87.39± 0.26, 81.67± 0.23 and 86.19± 0.25). The antilipoxygenase activity (63) of fraction 17 is near to standard. Fraction 17 strongly inhibited COX-1 and COX-2 activity. Based on the results, fraction 17 had 13 different phytochemicals and exhibited strong antioxidant, anti-inflammatory and COX-1 and COX-2 activity, which may be due to a combination of all compounds or any one single compound. It can be concluded that the fractions of methanol extract of Loranthus micranthus have pharmaceutically important compound(s) and further research is needed to isolate each compound to know the exact pharmaceutical compound.
Keywords: antioxidant